Industrial-waste agave fibres in flame-retarded thermoplastic starch biocomposites. (15th November 2019) - Sanchez-Olivares, Guadalupe; Rabe, Sebastian; Pérez-Chávez, Ricardo; Calderas, Fausto; Schartel, Bernhard
Abstract: Flame-retarded biocomposites of thermoplastic starch and natural fibres are successfully processed according to state-of-the-art extrusion and injection moulding. Using agave fibres and henequen fibres recovered from local industrial waste is a convincing contribution to sustainability. A systematically varied set of biocomposites is investigated comprehensively, e.g. electron microscopy is used for characterizing the morphology, rheology for the melt viscosity, tensile and impact resistance for the mechanical properties, thermal analysis for the pyrolysis, UL 94 burning chamber and oxygen index for the flammability, and cone calorimeter for the fire behaviour. Achieving sufficient mechanical properties was not the goal in our pre-competitive study but may be tackled by adding compatibilizer in future. The combination of well-dispersed natural fibres, aluminium diethylphosphinate (AlPi) and a special silicone synergist (Si) is proposed as promising innovative route for V0-classified biocomposites. The flame-retardancy modes of action in the gas phase (fuel dilution and flame inhibition) and in the condensed phase (charring, protective layer formation) are discussed in detail, as is the role of combining the ingredients. This work is a convincing proof of principle of how to prepare industrial-waste fibres biocomposites, to apply the synergistic combination of AlPi and Si for future flame-retarded technical polymer materials that are based on renewable resources and compostable.